In vitro transcription of RU, a middle repetitive element of the rat genome. - Page, G (1986)
Repetitive DNA sequences have been found within as well as adjacent to the rat growth hormone (rGH) gene (1,2). In vitro transcription of the rGH gene yields transcripts predominantly from a tandemly duplicated repeat (RU) in the second intron of the gene. The relative alpha-amanitin sensitivity of this transcription indicates that it is carried out by RNA polymerase III. Transcription initiates within a 5' flanking 15 base-pair repeat, and terminates within a stretch of A residues at the end of each repeat, a termination site that is notably unlike most of those used by polymerase III. Approximately 75% of the transcripts stop at the end of the first repeat; the remainder "read-through" to a homologous termination region at the end of the second repeat.